Aesthetics of Interactions by Nicolas Bourriaud in the View of Criticism and Search for an Alternative - Lvovna Panchenko, Olga (2020)
Art critics and artists conduct an intensive search in defining the tasks of artistic creation. Culture is undergoing a major shift in the field of modern art towards social interaction. What achievements have been made in the field of social art, as defined in the aesthetics of the interactions of "? How does critical thought develop in contemporary foreign art? What are the requirements of the art practices of critics Miwon Kwon, Maria Lind, Claire Bishop? In order to answer these questions, the authors examine the works of social artists, as well as the writings of critics, in which an alternative to the views of N. Bourriaud is expressed.